Prevalence, predictors, and economic burden of mental health disorders among asylum seekers, refugees and migrants from African countries: A scoping review. - Wael Osman; France Ncube; Kamil Shaaban; Alaa Dafallah (PLoS ONE)
Background Asylum seekers, migrants, and refugees from African countries may have significant health needs, resulting in economic implications for receiving countries around the world. The risk of mental illness is higher in these communities because of factors like violence, deprivation, and post-immigration challenges. Objective The purpose of this study was to examine the literature to determine the prevalence, predictors, and economic impacts of mental health (MH) disorders among asylum seekers, migrants, and refugees from African countries. Design and methods In this scoping review, we followed the guidelines from PRISMA and CoCoPop. A modified version of the Appraisal Tool for Cross-Sectional Studies (AXIS) was used to assess study quality for cross-sectional studies, while an appraisal list was used for qualitative studies based on the Critical Appraisal Skills Programme (CASP). Inclusion criteria included peer-reviewed articles published in English, and articles based on official reports from credible institutions and organizations. Among the exclusion criteria were publications that were not peer reviewed or had not been sourced by credible sources, publications that did not meet the study topic or language criteria, mixed populations (including Africans and non-Africans), and research abstracts, reviews, news articles, commentary on study protocols, case reports, letters, and guidelines. Data sources A systematic search was carried out in Medline (via PubMed), EMBASE, APA PsycINFO, Web of Science and EBSCO, to identify relevant articles that were published between 1 January 2000 and 31 January 2024. Results A total of 38 studies met the inclusion criteria, including 22 from African countries and three qualitative studies. In terms of number of countries contributing, Uganda was the largest (n = 7), followed by Italy (n = 4). The most studied conditions, using multiple diagnostic tools, were Post-Traumatic Stress Disorder (PTSD, n = 19) and depression (n = 17). These studies all revealed elevated rates of mental health disorders among these groups, and these were related to migration, refugee-related factors, and traumatic events. Most of these groups are dominated by young males. There is, however, a prominent presence of minors and women who have suffered a variety of forms of violence, in particular sexual violence. Furthermore, mental illnesses, such as PTSD and depression, are not only persistent, but can also be transmitted to children. In accordance with our inclusion criteria, our review found only one study that examined the economic impact of MH disorders in these groups, leaving a significant knowledge gap. According to this randomized controlled trial, intervention to reduce psychological impairment can help young people stay in school, improve their quality-adjusted life year (QALY), and earn an incremental cost-effectiveness ratio (ICER) of $7260 for each QALY gained. Conclusion Asylum seekers, migrants, and refugees from African countries are likely to experience MH needs, according to this scoping review. As well as posing persistent challenges, these disorders can also be transmissible to offspring. In addition to longitudinal studies of these groups, economic impact studies of mental illnesses are necessary.